2009
DOI: 10.1038/ncb1978
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the γ-secretase interactome and validation of its association with tetraspanin-enriched microdomains

Abstract: Gamma-secretase, an aspartyl protease that belongs to the iCLiPs (intramembrane cleaving proteases) family, is a multiprotein complex that consists of presenilin (PS), nicastrin (NCT), Aph-1 and Pen-2 (ref. 1). It is responsible for generation of the beta-amyloid peptide (Abeta), the primary component of senile plaques in the brains of patients with Alzheimer's disease. Although the four components are necessary and sufficient for gamma-secretase activity, additional proteins are possibly involved in its regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
129
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 32 publications
8
129
0
Order By: Relevance
“…The regulation and maturation of the activity of the ␥-secretase complex could possibly be maintained by the G-protein scaffold protein, tetraspanin (15). Interestingly, this same study pulled out interactions of PS1 with components of the OST, in particular OST48 and ribophorin II.…”
Section: Discussionmentioning
confidence: 83%
“…The regulation and maturation of the activity of the ␥-secretase complex could possibly be maintained by the G-protein scaffold protein, tetraspanin (15). Interestingly, this same study pulled out interactions of PS1 with components of the OST, in particular OST48 and ribophorin II.…”
Section: Discussionmentioning
confidence: 83%
“…S4e,f). The recent demonstration that CD9P-1, CD9 and CD81 associate with the g-secretase complex 40 raised the hypothesis that these molecules could increase the fusion by regulating the Notch pathway, which has a key role in the balance between self-renewal of satellite cells and their engagement towards differentiation 41 . Indeed, g-secretasemediated cleavage of Notch is an essential step of this pathway 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In view of the proposed role of tetraspanins in establishing or maintaining membrane microdomains, Wakabayashi et al (14) suggested that CD9 and CD81 modulate the proteolytic activity of γ-secretase or its interaction with β-APP. We favor a similar model in which members of the RDS subfamily of tetraspanins promote γ-secretase activity through promoting physical association between γ-secretase and Notch in membrane microdomains.…”
Section: Discussionmentioning
confidence: 99%
“…Wakabayashi et al (14) reported that two tetraspanins of the CD subfamily, CD9 and CD81, physically associate with γ-secretase and also showed that CD81 RNAi reduces γ-secretase processing of β-APP. We assessed the effect of depleting the activity of CD9 or CD81 individually in HeLa cells by RNAi and measured the effect on the activity of different leukemic mutant forms of NOTCH1 as above in two separate experiments.…”
Section: Reduction Of Cd9 or Cd81 Does Not Reduce The Activity Of Leumentioning
confidence: 99%
See 1 more Smart Citation